The Role of Babinsa as Street-Level Bureaucrats in COVID-19 Handling through a Collaborative Governance Approach - Syarief Syah Banjar; Agus Heruanto Hadna; Muhadjir Darwin; Pande Made Kutanegara (GoAcademica Research & Publishing, 2023)
Indonesia is one of the countries that has been severely affected by the COVID-19 pandemic and ranks 20th among the countries with the highest number of COVID-19 cases. Like other countries, COVID-19 has also negatively impacted various sectors of society, including social, cultural, economic, and educational aspects. The Indonesian government has implemented various policies from the central to the village level, such as movement restrictions through partial lockdown policies, the implementation of health protocols, COVID-19 patient management through testing, tracing, treatment, and vaccination. The complex and frequently changing policies, adjusted according to the latest COVID-19 situation, often cause confusion among the public and, in turn, lead to some people's neglectful attitudes. In dealing with the complexity of policies and their implementation, the role of street-level bureaucrats, specifically Babinsa, who are part of the Indonesian Army (TNI AD) and serve at the village level, becomes crucial. This study aims to delve into the role of Babinsa as street-level bureaucrats and the dynamics of grassroots-level COVID-19 handling through actor collaboration. The study concludes that Babinsa collaborates with village governments, healthcare workers, religious leaders, community figures, and the business community in performing their roles to strengthen capacity and resources in managing COVID-19. Additionally, the study identifies various factors that influence the performance of Babinsa as street-level bureaucrats in the implementation of COVID-19 handling policies, including sectoral ego, budget constraints, community characteristics, and limited healthcare personnel.